THE EFFECT OF DIGITAL STORYTELLING ON CUSTOMER ENGAGEMENT AND BRAND AWARENESS AMONG GENERATION Z - Nur Hidayat; Arweni Arweni; Febrianawati Febrianawati; Yuana Yuana; Vini Ramadhani (LPPM STIE Muhammadiah Bandung, 2026)
This research investigates the impact of digital storytelling on customer engagement and brand awareness among Generation Z social media users in Indonesia. Recent studies indicate that immersive, character-driven, and authentic digital narratives enhance emotional attachment, cognitive processing, and behavioral responses, subsequently influencing engagement and brand-related outcomes. A quantitative explanatory design was utilized, with data gathered via an online survey targeting active Generation Z social media users who engaged with digital storytelling content. Structural Equation Modeling was employed to analyze the data, examining the direct and mediating effects among digital storytelling, customer engagement, and brand awareness. The findings demonstrate that digital storytelling significantly influences customer engagement and has a moderate direct impact on brand awareness, whereas customer engagement strongly enhances brand awareness. Mediation analysis indicates that customer engagement serves as a partial mediator in the relationship between digital storytelling and brand awareness, with a significant portion of the total effect conveyed through engagement. The findings indicate that digital storytelling strategies should focus on enhancing cognitive, affective, and behavioral engagement to establish sustainable brand awareness within Generation Z.